Spending on Instructional Staff Support Among Big City School Districts: Why Are Urban Districts Spending at Such High Levels? - Kieran M. Killeen; David H. Monk; Margaret L. Plecki (Educational Considerations, 2000)
In a recent study conducted under the auspices of the Center for the Study of Teaching and Policy (CTP), we found that U.S. school districts, on average, direct 2.8% of their annual budgets toward what the Census Bureau defines as instructional staff support.